Plasmablastic Lymphoma in an Immunocompetent Patient with MDS/MPN with Ring Sideroblasts and Thrombocytosis—A Case Report. (4th November 2018) - Bouchla, Anthi; Papageorgiou, Sotirios G.; Tsakiraki, Zoi; Glezou, Eirini; Pavlidis, George; Stavroulaki, Georgia; Bazani, Efthimia; Foukas, Periklis; Pappa, Vasiliki
Abstract : Plasmablastic lymphoma (PBL) is a rare, aggressive type of B-cell non-Hodgkin lymphoma with the vast majority of patients responding poorly to treatment or progressing shortly thereafter. Cyclophosphamide-doxorubicin-vincristine-prednisolone (CHOP) or CHOP-like regimens have disappointing results in this setting. We report a case of PBL arising in a previously diagnosed myelodysplastic/myeloproliferative (MDS/MPN) with ring sideroblasts and thrombocytopenia (RS-T), HIV-negative patient treated with the combination of CHOP and bortezomib. The patient achieved complete metabolic response, which has lasted one year, longer by far than would have been expected with the sole use of CHOP.